Terrorism the philosophical issues - Primoratz, Igor (Palgrave Macmillan, 2004)
Also included are four case studies, showing how the concepts and arguments philosophers deploy in discussing violence, war and terrorism apply to particular instances of both insurgent and state terrorism, ranging from World War II to September 11, 2001.